Economic analysis and law : the economics of the courtroom - Warburton, Christopher E. S. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"A comprehensive presentation of the use of economics in judicial decisions, the book is structured to provide all of the foundational concepts that are important for the application of economics to the development and interpretation of statutes that emanate from economic conditions. The diversity of the economic field defines the scope of the book and its relevance to the study of law and rule adjudication. Beyond the positive dimensions of law and economics, the book evaluates the normative aspects of law and economics when laws are imprecise, and markets are inefficient. The ethical scope of transactions and rule adjudication are further considered in the context of professional ethics and the rationale for ethical considerations in the practice of law and economics. It presents a unique analysis of law, finance, and economics, by taking a look at the intricate quantitative requirements that are essential for scientific knowledge in the courtroom and the international dimensions of the practice of law and economics beyond municipal frontiers. It alerts entrepreneurs to risk exposures in the global economy and provides foundational information for readers who are also interested in international law and economics, and the essence and interpretations of international conventions appertaining to money, expropriation, the environment, and investments in international financial markets. This book is a useful reference for both undergraduate and graduate students who are interested in law and economics, forensic economics, corporate white-collar crime, and legal studies. It is also valuable for certificate programs for paralegals who wish to have a basic understanding of economic and financial concepts"--
Introduction -- Microeconomic foundation -- Macroeconomics in forensic economics -- Corporate financial analysis and investment law -- Innovation and expropriation of creative rights -- Econometrics for the courtroom -- Tax avoidance and evasion -- US Antitrust law and enforcement -- International economics in international courts of law.
OCLC-licensed vendor bibliographic record.
Keywords: Law and economics; Forensic economics; Law -- Economic aspects -- United States; BUSINESS & ECONOMICS / Economics / Microeconomics; LAW / Legal Education; BUSINESS & ECONOMICS / Business Law